Neutrophil hypersegmentation and thrombocytosis in children with iron deficiency anemia - Düzgün, Serpil; Yildirmak, Yildiz; Cetinkaya, Feyzullah (The Turkish Journal of Pediatrics, 2005)
Neutrophil hypersegmentation is an expected peripheral blood smear finding in megaloblastic anemias. But some clinical reports suggest that neutrophil hypersegmentation may also occur in patients with iron deficiency anemia. In this study we searched the presence of neutrophil hypersegmentation and thrombocytosis in patients with iron deficiency anemia but who had normal serum vitamin B12 and folic acid levels. The study comprised 102 patients with iron deficiency anemia and 21 age-matched healthy controls. All routine tests for iron deficiency anemia were done, serum folate and cobalamin levels were measured, and platelets were counted in all patients and controls. Peripheral blood smears were examined for neutrophil hypersegmentation. Hypersegmentation was found in 30.4% of anemic patients and in 9.5% of controls (p < 0.05). The number of platelets was also significantly higher in anemic children (p < 0.05). These results show that neutrophil hypersegmentation may also be seen in patients with iron deficiency anemia, and thrombocytosis is a common laboratory finding in this disorder.